Utilizing Stakeholders Analysis on Sustainable Organic Farming in West Java: The Case of Cisarua Organic Farming - Prasetyaningtyas, Sekar Wulan; Sobir, Sobir; Hermawan, Aji; Maarif, M. Syamsul (School of Business, Bogor Agricultural University (SB-IPB), 2019)
There has been an increase in demand for organic products in Indonesia along with the incessant slogan of healthy living. In terms of small farmers, organic farming is proven to provide increased income, unfortunately, there is no clear system and strategy in developing organic agriculture in Indonesia. The purpose of this research was to understand the role of key stakeholders in Cisarua Horticulture Organic Farming. Stakeholder analysis used in this research to get knowledge about the actors, their behavior, relationships and their influence on decision - making processes. The information is used to develop the farm strategies, to reach the farm goals and to assess the feasibility of policy directions. The methodology used is the Soft System Methodology (SSM). SSM is an organizational process modeling method that can be used for general problem resolution and change management. Rich picture, Root definitions, and conceptual model were presented in the paper. Data were taken using focus group discussion and in-depth interviews with the farm staffs, farmers of the sustainable horticulture organic farming farm in Cisarua, Indonesia, and national organic farming association. From Stakeholders analysis, four main results were obtained: identifying the relationship among stakeholders; conflicts among them; the stakeholders’ role in farm; and the stakeholders’ interest towards farm program. In conclusion; focusing on one hauler only, investing in seed horticulture products, improving the quality of horticulture products, and mentoring for small-scale farmers were identified as a critical action for the strategy in the organic farming farm in Cisarua, Indonesia. The policy implications of this research are basically to see the contribution of actors in making a strategy.